Oxygen-incorporated 3D flower-like MoS2 microsphere as a bifunctional catalyst for effective synthesis of 2, 5-diformyfuran from fructose. Issue 8 (15th March 2023) - Yang, Zhenzhen; He, Yuhan; Tang, Pengfei; Xu, Chenhui; Zhang, Genlei; He, Jianbo
Abstract : An oxygen-incorporated 3D flower-like MoS2 microsphere was prepared by a simple hydrothermal procedure and served as a highly active catalyst in the synthesis of DFF from fructose. Abstract : It is challenging to effectively convert fructose to 2, 5-diformylfuran (DFF) over a simple and low-cost bifunctional catalyst. In this study, an oxygen-incorporated 3D flower-like MoS2 microsphere is prepared by a simple hydrothermal procedure and serves as a highly active bifunctional catalyst exhibiting both acidity and oxidability, which contribute to the dehydration of fructose to HMF and the aerobic oxidation of HMF to DFF, respectively. A DFF yield of 98.1% with a HMF conversion of 100% is achieved in the aerobic oxidation of HMF to DFF catalyzed by MoS2 under the optimum reaction conditions. Based on the experimental and catalyst characterization results, a possible reaction mechanism that involved Mo 6+ /Mo 4+ is proposed for MoS2 -catalyzed oxidation of HMF to DFF. Then, MoS2 is used as a bifunctional catalyst for direct conversion of fructose to DFF, achieving a high DFF yield of 81.3% by a "one-pot, two-step" strategy. Importantly, the as-prepared MoS2 catalyst reveals no significant change in five consecutive reaction runs demonstrating the excellent stability of the catalyst.